Assessing the socioeconomic impact of ECOWAS CET implementation in Niger - Fofana, Ismaël (Wageningen Academic Publishers, 2018)
The fifteen Member States of the Economic Community of the West African States (ECOWAS) adopted on October 2013 a Common External Tariff (CET) with the aim of strengthening and accelerating regional integration. Niger is among the first countries to implement the ECOWAS CET scheme on April 2015. This study assesses the ex-ante economic impact for Niger of a successful implementation of the CET scheme by the fifteen Member States. It uses fifteen single-country computable general equilibrium models interconnected through the trading of commodities and the mobility of labor and capital. A welfare improving impact is simulated for Niger. Custom union is welfare improving if the benefits of trade creation overcome the costs of diverting trade. Indeed, Niger expands its trade with both ECOWAS and non-ECOWAS partners more rapidly under the CET compared to the continuity, i.e. CET scheme not implemented.